Cognitive plasticity in normal and pathological aging - Fernández-Ballesteros, Rocío (Dove Medical Press, 2012)
The main goal of the present study is to examine to what extent age and cognitive impairment contribute to learning performance (cognitive plasticity, cognitive modifiability, or learning potential). To address this question, participants coming from four studies (Longitudinal Study of Active Aging, age range, 55–75 years, N = 458; Longitudinal Study in the very old [90+], age range, 90–102, N = 188, and Cognitive Plasticity within the Course of Cognitive Impairment, 97 “Normal”, 57 mild cognitive impairment [MCI], and 98 Alzheimer’s disease [AD] patients) were examined through a measure of verbal learning (developed from Rey). The results show that all age, MCI, and AD groups learned across the five learning trials of that test, but significant differences were found due to age, pathology, and education. The effects of pathology (MCI and AD) can be expressed in a metric of “years of normal decline by age”; specifically, being MCI means suffering an impairment in performance that is equivalent to the decline of a normal individual during 15 years, whereas the impact of AD is equivalent to 22.7 years. Likewise, the improvement associated with about 5 years of education is equivalent to about 1 year less of normal aging. Also, the two pathological groups significantly differed from “normal” groups in the delayed trial of the test. The most dramatic difference is that between the “normal” group and the AD patients, which shows relatively poorer performance for the AD group in the delayed trial than in the first learning trial. The potential role of this unique effect for quick detection purposes of AD is assessed (in the 75–89 years age range, sensitivity and specificity equal 0.813 and 0.917, respectively).